Implementing the Resource Sharing Innovation Model to Sustainably Address the High Unemployment Rate - Suseno, Bambang Dwi; Yusuf, Furtasan Ali; Hidayat, Syamsul; Surani, Dewi (KnE Social Sciences, 2021)
There is a paradoxical condition in which Banten Province is an area with an abundance of manufacturing companies, but has a high unemployment rate. So it is important to carry out research to provide innovative and sustainable policy mix recommendations for local governments. This study aims to analyze (1) the relationship between training revolving funds and the competence of vocational school graduates, (2) the relationship between training revolving funds and the skill development center, (3) the relationship between the competence of vocational school graduates and the skill development center, (4) the relationship between the competence of vocational education graduates and resource sharing innovation, (5) the relationship between resource sharing innovation and skill development centers, (6) resource sharing innovation with industrial human competitiveness, and (7) the effect of development center skills on industrial human competitiveness. This study used Research and Development (R&D) methods with participants from selected companies who were willing to accept vocational graduates as apprentices. After the data were collected, they were processed using the IBM AMOS 2.2 application. The findings were confirmed through triangulation with the person in charge of apprenticeships at the seven participating companies. The willingness to do resource sharing innovation (RSI) had an effect on the competitiveness of industrial people. Based on these results, it can be concluded that RSI, offered as a novelty, can increase the competitiveness of industrial people. These results can be used to overcome the high unemployment rate through RSI from companies in the region providing business convenience incentives. Keywords: resource sharing innovation, unemployment, sustainability